2011
DOI: 10.1021/jp109669t
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Protection of Carbon-Encapsulated Magnetic Nickel Nanoparticles through a Sucrose-Based Synthetic Strategy

Abstract: We report an easy synthesis strategy for the incorporation of carbon-coated Ni nanoparticles within the pores of a highly porous carbon matrix. An advantageous feature of this process is that it is able to provide large amounts of magnetic Ni composite by means of an easy-to-follow one-pot reaction. While a typical chemical route based on a conventional pyrolysis procedure gives rise to NPs with Ni@NiO (core@shell structure), the addition of sucrose to the synthesis mixture and its subsequent transformation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Similar findings come from the paper by Schumacher et al, which described that concentrated aqua regia results in severe perforation of carbon coatings and leads to the dissolution of pristinely encapsulated magnetic nanoparticles [13]. Furthermore, Fernandez-Garcia et al [14] studied the stability of carbon-coated nickel nanoparticles embedded in the pores of mesoporous carbon matrix. They demonstrated that 0.1 M HCl does not etch the magnetic phase.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar findings come from the paper by Schumacher et al, which described that concentrated aqua regia results in severe perforation of carbon coatings and leads to the dissolution of pristinely encapsulated magnetic nanoparticles [13]. Furthermore, Fernandez-Garcia et al [14] studied the stability of carbon-coated nickel nanoparticles embedded in the pores of mesoporous carbon matrix. They demonstrated that 0.1 M HCl does not etch the magnetic phase.…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, they observed that carbon coating perfectly protected the nickel core from the aerial oxidation even for 36 months. Similarly, Schwickardi et al [15] studied carbon-coated iron nanoparticles surrounded by activated carbon and obtained similar results to paper [14]. The work of Haslam et al [16] also confirmed that thin films formed of nickel nanocrystals encapsulated in carbon had well corrosion stability in hot 1.5 M sulfuric acid.…”
Section: Introductionmentioning
confidence: 69%
“…[1][2][3][4][5][6][7] The growing research activity in this field has been propelled by the development of new chemical routes that allowed the synthesis of NPs with tuneable size distributions and being embedded in different insulating matrices. [8][9][10][11][12][13][14][15][16] It is worth noting that NPs of the same material and similar size but synthetized using different fabrication routes show a strong dependence of the magnetic properties on the morphology, microstructure or the nature of the matrix. 1,8,10,13 Moreover, 3d metal oxide NPs with different core-shell morphologies are also good candidates for a number of applications due to the possibility of tuning the magnetic response and/or the coating with a functional layer.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of spatially confined stability, the encapsulation of Ni nanoparticles into an individually isolated form within porous supports, such as carbon materials, hollow SiO 2 capsules, or the inner walls of Al 2 O 3 nanotubes, has proved to be an effective strategy to enhance their stability because these porous structures can isolate catalytically active Ni sites to a large extent and dramatically decrease the aggregation and loss of Ni nanoparticles. Moreover, yolk–shell nanostructures, with an inner movable magnetic core or multiple inner movable magnetic cores and an outer hollow shell, have been proven to be good supports for metal nanoparticles due to their facile magnetic recoverability and high specific surface area …”
Section: Introductionmentioning
confidence: 99%